2012
DOI: 10.1093/rheumatology/ker519
|View full text |Cite
|
Sign up to set email alerts
|

Certolizumab pegol plus MTX administered every 4 weeks is effective in patients with RA who are partial responders to MTX

Abstract: CZP 400  mg every 4 weeks plus MTX demonstrated a favourable risk-benefit profile with rapid onset of action in RA patients with an inadequate response to an earlier MTX therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(33 citation statements)
references
References 13 publications
0
32
0
1
Order By: Relevance
“…All anti-TNF␣ biologic agents (infliximab [IFX], adalimumab, etanercept, golimumab and certolizumab) are implicated in the formation of anti-drug antibodies (ADAs) [1][2][3][4][5][6]. Nevertheless, ADAs to etanercept are absent or are detected at low levels [4,7,8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…All anti-TNF␣ biologic agents (infliximab [IFX], adalimumab, etanercept, golimumab and certolizumab) are implicated in the formation of anti-drug antibodies (ADAs) [1][2][3][4][5][6]. Nevertheless, ADAs to etanercept are absent or are detected at low levels [4,7,8].…”
Section: Introductionmentioning
confidence: 99%
“…Thymic or central tolerance probably represents in part the origin of the reduction in immunogenicity provided by the humanization of therapeutic monoclonal antibodies. However, as illustrated by the large number of cases of ADAs to chimeric, humanized and fully human antibodies [5,6], humanization is not sufficient to confer a total lack of immunogenicity. Several reports indicate that the repertoire of naive CD4+ T lymphocytes resulting from thymic education and present at the time of the injection shapes the immunogenicity degree and the amplitude of the potential T cell response against biologic drugs [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…En pacientes con AR y respuesta insuficiente (RI) al MTX existe evidencia (NE 1a) para los 9 agentes biológicos disponibles en España (abatacept, adalimumab, anakinra, certolizumab, etanercept, golimumab, IFX, rituximab y tocilizumab), que confirma el efecto de rescate y la mayor eficacia terapéutica de la combinación FAME biológico + MTX frente a la continuación de la terapia con MTX en monoterapia [111][112][113][114][115][116] . En esta situación clínica, la combinación FAME biológico + MTX vs. MTX presenta un riesgo relativo (RR) de alcanzar la respuesta ACR70 de 4,07 (IC 95%: 3,21-5,17).…”
Section: Resultados Y Discusiónunclassified
“…Thus, six RCTs including 3349 patients (1556 efficacy-related events and 137 safety-related events) met the inclusion criteria (. Table 1; [9][10][11][12][13][14] Fig. 1).…”
Section: Studies Included In the Metaanalysismentioning
confidence: 99%
“…Several clinical trials have attempted to evaluate the efficacy and safety of CZP + MTX in patients with active RA who had an incomplete response to MTX or disease-modifying antirheumatic drug (DMARD) [9][10][11][12][13][14]. A previous metaanalysis showed that CZP was effective in active RA patients and had a manageable safety profile [15].…”
Section: Introductionmentioning
confidence: 99%